On the implementation of SPMD applications using Haskell/sub #/ - Carvalho, F. H. de; Lins, R. D.; Quental, N. C. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2003)
Commodities-built clusters, a low cost alternative for distributed parallel processing, brought high-performance computing to a wide range of users. However, the existing widespread tools for distributed parallel programming, such as messaging passing libraries, does not attend new software engineering requirements that have emerged due to increase in complexity of applications. Haskell/sub #/ is a parallel programming language intending to reconcile higher abstraction and modularity with scalable performance. It is demonstrated the use of Haskell/sub #/ in the programming of three SPMD benchmark programs, which have lower-level MPI implementations available.